اباحت اصلیہ کا اصول اور اس کی وسعت ۔ ایک تحقیقی جائزہ: The Principle of Ibaḥat-e-Aṣliah (Permissibility by Default) and its Scope -A Research Based Study - Dr. Numan Anwar; Dr. Hafiz Abdul Basit Khan (jihat-ul-islam, 2021)
Islam is a complete system of life. Allah Almighty has made some things lawful and some unlawful. But there are many things in the universe that are permissible and there are no explicit texts about them. The research question that has been addressed in this article is that what are the limits, scope, importance and modern application of this principle: Ibaḥat-e-Aṣliah (Permissibility by Default) especially in the context of halāl food and cosmetic industry. The writers at first has provided its explanation in the light of Qur’an and Sunnah and the sayings and opinions of the jurists. Then, exceptions of this principle have been discussed in full length. And finally, some important rules regarding the application of the said rule with modern examples have been also discussed. As a result, it is understood that there is real immorality in things and the things that have been declared halāl by the Shari’ah are halāl, and the things that have been declared harām by the Shari’ah are harām. Moreover, the things that have been silenced, If no ruling has been given about them, it will be permissible. Considering something as illegitimate or harām simply because it is not mentioned or due to lack of evidence is contrary to the Shari’ah and deviates from the system of status and sanctity prescribed by Islam, because the silence of the Shari’ah on something is itself an indication that the thing is permissible. In Islam, the status of a Shari’ah belongs only to Allah (SWT) and Muhammad (peace be upon him). In order to give the believers an orderly life, certain things that were harmful to them have been declared harām